New species and new records of Monohelea Kieffer from eastern Amazon, Brazil (Diptera: Ceratopogonidae) - Felippe-Bauer, Maria Luiza; Cardoso, Erick Aragão; Trindade, Rosimeire Lopes Da (Zootaxa, 2017)
Seven new species of Monohelea Kieffer are described and illustrated and new records from M. affinis Felippe-Bauer & Spinelli, M. guaimiesi Lane & Wirth and M. maculipennis (Coquillett) are given based on specimens collected in Pará State, eastern Brazilian Amazon. The new species are compared with their similar congeners and the distributional records of both new and previously described species are presented in Figure 1. A key for identification of the Brazilian Amazonian species of Monohelea is also provided.